Seize the book, jail the author : Johann Lorenz Schmidt and censorship in eighteenth-century Germany - Spalding, Paul (Purdue University Press, 1998)
"Under the patronage of two south German nobles, Johann Lorenz Schmidt published an annotated translation of the Bible's opening books in 1735"--Provided by publisher